2004
DOI: 10.1242/dev.00965
|View full text |Cite
|
Sign up to set email alerts
|

Hexhomeobox gene-dependent tissue positioning is required for organogenesis of the ventral pancreas

Abstract: In animal development, digestive tissues emerge from different positions of the endoderm as a result of patterning signals from overlying mesoderm. Although embryonic tissue movement during gastrulation generates an initial positional relationship between the endoderm and mesoderm, the role of subsequent endoderm movement against the mesoderm in patterning is unknown. At embryonic day 8.5 in the mouse, proliferation of cells at the leading edge of ventral-lateral endoderm, where the liver and ventral pancreas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
191
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(199 citation statements)
references
References 53 publications
(78 reference statements)
5
191
1
2
Order By: Relevance
“…This finding suggests that rs1111875 may be more likely to be one of the genetic factors involved in beta cell compensatory insulin secretion in the face of insulin resistance induced by pregnancy. It is known that HHEX is expressed at high levels in the fetal and adult pancreas [23] and is crucial for the development of the ventral pancreas [46]. In Europids [20][21][22][23], rs1111875 is found within an extended region of linkage disequilibrium that contains not only HHEX but also KIF11 and IDE.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that rs1111875 may be more likely to be one of the genetic factors involved in beta cell compensatory insulin secretion in the face of insulin resistance induced by pregnancy. It is known that HHEX is expressed at high levels in the fetal and adult pancreas [23] and is crucial for the development of the ventral pancreas [46]. In Europids [20][21][22][23], rs1111875 is found within an extended region of linkage disequilibrium that contains not only HHEX but also KIF11 and IDE.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking the relative movement of the ventral lateral foregut endoderm (the prospective ventral pancreas) prevents ventral pancreas specification from occurring. It was the genetic dissection of Hhex function in the mouse that led to this connection being made, with the tissue's ''escape/repositioning'' process being promoted by an Hhex-dependent proliferation of the leading edge of endoderm to allow it to rapidly extend away from the influence zone of the cardiac mesoderm (Bort et al, 2004). How extrinsic cues affect cell-fate specification needs to be considered as a highly dynamic, level-and context-dependent process.…”
Section: Ventral Pancreas Inductionmentioning
confidence: 99%
“…40 Although the absence of hepatic markers in Hex-null embryos at E9.5 would be consistent with a failure in hepatic specification, recent analysis of Hex Ϫ/Ϫ ventral endoderm from E8.5 embryos containing 10 somite pairs found that Alb, Ttr, and Prox1 could in fact be detected by reverse-transcriptase polymerase chain reaction. 41 Moreover, cardiogeneic mesoderm was capable of inducing hepatic markers within the Hex Ϫ/Ϫ endoderm in cultured tissue explants. Although hepatic markers were expressed, the proliferation of the specified endodermal cells was markedly reduced in Hex Ϫ/Ϫ embryos.…”
Section: From Where Do Hepatic Cells Arise?mentioning
confidence: 99%
“…Although hepatic markers were expressed, the proliferation of the specified endodermal cells was markedly reduced in Hex Ϫ/Ϫ embryos. 41 These studies imply that although Hex is dispensable for induction of hepatic development, it is essential for expansion of the nascent hepatoblast population. In addition to being essential for development of the early liver bud, studies in chick embryos have shown that expression of Hex in the ventral endoderm requires both FGF and BMP signaling.…”
Section: From Where Do Hepatic Cells Arise?mentioning
confidence: 99%